Fine-needle aspiration washout in the diagnosis of cystic parathyroid adenoma. Issue 3 (10th March 2020) - Aliyev, Anar; Ismayilov, Rashad; Musayev, Jamal; Yusifov, Sabuhi
Abstract : Cystic parathyroid adenomas are one of the rare causes of neck masses. Due to its rarity, it causes misdiagnosis and wrong treatments and has undesirable consequences. The measurement of parathyroid hormone in fine-needle aspiration washout fluid is a minimally invasive, safe method for the diagnosis of parathyroid cysts and seems to be more useful than Tc-99m sestamibi (MIBI) parathyroid single photon emission computed tomography (SPECT)/CT.